Is leisure sedentary time associated with mental health issues? Evidence from China Health and Nutrition Survey - Li, Hao; Zeng, Weihong (Frontiers in Public Health, 2025)
BackgroundThe relationship between leisure sedentary behaviors and mental health remains inconclusive. This study aims to provide evidence on leisure sedentary behaviors on mental health using longitudinal data, along with its moderating and mediating roles.MethodsWe utilized data from four waves (2006–2015) of the China Health and Nutrition Survey (CHNS), focusing on adults who completed their education, with a total sample of 23,693 observations. Leisure sedentary time, the independent variable, was measured based on self-reported data, while mental health issues were the dependent variables based on the Simplified Symptom Self-Rating Scale (SCL) and the Perceived Stress Scale (PSS-14). The primary analysis employed ordinary least squares (OLS) regression. Potential endogeneity was addressed by instrumental variable (IV) method via two-stage least squares (2SLS) regression and a continuous difference-in-differences (DID) design.ResultsOur findings indicate that high levels of sedentary time are associated adversely with mental health issues. Moderating roles show that improving health literacy and reducing sedentary time were effective in alleviating this adverse impact. Among older adults, social engagement and support from female caregivers showed greater potential to reduce the detrimental mental health impact of leisure sedentary time. Furthermore, obesity serve as its mediating role.ConclusionThis study highlights the potential adverse impact of increased leisure sedentary time on mental health among Chinese population. These results provide a foundation for public health initiatives aimed at addressing the rising prevalence of sedentary behavior and its association with mental health issues.